2022
DOI: 10.1186/s12912-022-01004-y
|View full text |Cite
|
Sign up to set email alerts
|

Causes of futile care from the perspective of intensive care unit nurses (I.C.U): qualitative content analysis

Abstract: Background Medical care that has therapeutic effects without significant benefits for the patient is called futile care. Intensive Care Units are the most important units in which nurses provide futile care. This study aimed to explain the causes of futile care from the perspective of nurses working in Intensive Care Units are. Method The study was conducted using a qualitative approach. Qualitative content analysis was used to analyze the data. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…While medical futility is inherently ambiguous and contextdependent, hinging on probabilistic determinations of whether a treatment would benefit a patients' quality of life or offer a chance of recovery balanced against the risk of harm, it is also one of the primary drivers of moral distress among intensive care unit workers (Palda et al, 2005;Asayesh et al, 2018;Rakhshan et al, 2022). In the case of COVID-19 presented here, futility took on a somewhat different character.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…While medical futility is inherently ambiguous and contextdependent, hinging on probabilistic determinations of whether a treatment would benefit a patients' quality of life or offer a chance of recovery balanced against the risk of harm, it is also one of the primary drivers of moral distress among intensive care unit workers (Palda et al, 2005;Asayesh et al, 2018;Rakhshan et al, 2022). In the case of COVID-19 presented here, futility took on a somewhat different character.…”
Section: Discussionmentioning
confidence: 91%
“…Medical futility is an inherently ambiguous, multidimensional, and context-dependent concept that nevertheless generally describes a situation when a patients' physician has determined that a treatment offers no reasonable likelihood of benefit to the patients' quality of life or chance of recovery, and therefore providing such treatment would be not justified given the potential risk of harm (Palda et al, 2005;Asayesh et al, 2018;Rakhshan et al, 2022). Although futility is a concept as old as Hippocrates, the ethical dilemmas in making futility determinations endure and may even be amplified as new treatments emerge that extend a patients' life long after they otherwise would have died (Whitmer et al, 2009).…”
Section: Futilitymentioning
confidence: 99%
“…The patient's age is a characteristic that leads nurses even to provide futile care. 37 A study reported the age discrimination experience in healthcare centers in 30% of the elderly and 47% of the students. 38 In another study, the prioritization of medical care and treatment based on the patient's age was reported.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was conducted in 2022 using a qualitative research design with a conventional content analysis approach to examine Para medicine students' experiences of virtual education. This approach is a systematic and purposeful way to describe a phenomenon (19). This study was conducted on various fields of medical sciences (nursing, anesthesiology, operating room, midwifery, laboratory sciences) studying at universities in the north of Iran.…”
Section: Methodsmentioning
confidence: 99%